Applying the 2019 EULAR/ACR lupus criteria to patients from an established cohort: a Latin American perspective - Manuel Francisco Ugarte-Gil; Daniel Wojdyla; Guillermo J Pons-Estel; Bernardo A Pons-Estel; Graciela S Alarcón; Luis M Vila; Rosana Quintana; Veronica Saurit; Eloisa Bonfa; Enrique R Soriano; Russell Griffin; Guillermina B Harvey; et al. (RMD Open, 2020)
Objective To evaluate the performance of the 2019 European League Against Rheumatism (EULAR)/American College of Rheumatology (ACR) systemic lupus erythematosus (SLE) criteria in terms of earlier patients’ classification in comparison to the 1982/1997 ACR or the 2012 Systemic Lupus International Collaborating Clinics (SLICC) criteria.Materials and methods Patients from a Latin America, multiethnic, multicentre cohort, where SLE was defined using the physicians’ diagnosis, were included. To calculate the sensitivity of the 2019 EULAR/ACR criteria, the 1982/1997 ACR criteria were considered the gold standard. Additionally, comparison of the 1982/1997 ACR criteria and the 2012 SLICC criteria with the 2019 EULAR/ACR criteria was performed.Results The sensitivity of the 2019 EULAR/ACR criteria when compared with the 1982/1997 ACR criteria as the gold standard was 91.3%. This new set of criteria allowed an earlier SLE patient classification in 7.4% (mean 0.67 years) and 0.6% (mean 1.47 years) than the 1982/1997 ACR and the 2012 SLICC criteria, respectively. Patients accruing the 2019 EULAR/ACR earlier than the 1982/1997 ACR criteria were more likely to have high anti-dsDNA titres; those accruing them later were less likely to have mucocutaneous and joint manifestations; this was not observed when comparing them with the 2012 SLICC criteria.Conclusions The 2019 EULAR/ACR criteria classified earlier only a small proportion of Latin America patients than with the two other criteria sets in real-life clinical practice scenarios. Further studies in different patient populations are needed before these new criteria are adopted worldwide.